Čas epidemije in izposoja gradiva na portalu Biblos v Posavju - Dvornik, Andreja (Knjižnica, 2020)
Purpose: In this article, we present borrowing e-books from the web portal Biblos in libraries in Posavje region during the epidemic due to the increase of infected patients with coronavirus (SARS-CoV-2).Methodology/approach: We used a survey to gain information about inventory and borrowing e-books on the web portal Biblos in Brežice Library, Valvasor Library Krško and Sevnica Library. Information about the inventory and borrowing e-books in Brežice Library for past years was gained from the library’s annual reports.Results: Gained results show that libraries have a proportionately sizeable inventory of e-books, regarding the number of members. During the closure of libraries, they informed their members and users about their activities and supply of printed and online media and their websites and social media.Research limitations: Only libraries from Posavje region have been involved in the review – Brežice Library, Valvasor Library Krško and Sevnica Library. The data is focused only on a specific time frame during the lockdown of libraries for users between March 13 and May 3, 2020, and the period of stricter measures until the declaration of the end of the coronavirus epidemic on May 31, 2020. For comparison, we used the same period in 2019.Originality/practical implications: The results are useful for all three involved public libraries and all other libraries because they show the response of users to changed conditions of open access to literature and the success of redirecting readers to the web portal Biblos.
Keywords: Biblos; e-knjige; epidemija; izposoja; koronavirus; Posavje; spletni portali; splošne knjižnice